2014
DOI: 10.4196/kjpp.2014.18.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Scopoletin fromCirsium setidensIncreases Melanin Synthesis via CREB Phosphorylation in B16F10 Cells

Abstract: In this study, we isolated scopoletin from Cirsium setidens Nakai (Compositae) and tested its effects on melanogenesis. Scopoletin was not toxic to cells at concentrations less than 50 µM and increased melanin synthesis in a dose-dependent manner. As melanin synthesis increased, scopoletin stimulated the total tyrosinase activity, the rate-limiting enzyme of melanogenesis. In a cell-free system, however, scopoletin did not increase tyrosinase activity, indicating that scopoletin is not a direct activator of ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Compounds T1, T3-T8 spectral data were in agreement with the reported data of stigmasterol [21], scopoletin [22], eurycomalactone, 6 α - hydroxyeurycomalactone [23], eurycomanone [23], eurycomanol [23], and eurycomanol-2- O - β -D-glycopyranoside [24]. This is the first report for the isolation of T1 and T3 from E. longifolia and for the isolation of T2 from genus Eurycoma .…”
Section: Discussionsupporting
confidence: 88%
“…Compounds T1, T3-T8 spectral data were in agreement with the reported data of stigmasterol [21], scopoletin [22], eurycomalactone, 6 α - hydroxyeurycomalactone [23], eurycomanone [23], eurycomanol [23], and eurycomanol-2- O - β -D-glycopyranoside [24]. This is the first report for the isolation of T1 and T3 from E. longifolia and for the isolation of T2 from genus Eurycoma .…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, identification of a strategy for the protection of transplanted MSCs is important for the development of MSCs-based therapy for regenerative medicine. C. setidens is a phenolic and flavonoid compound, which possesses anti-inflammatory, anticancer, anti-mutation, anti-fungal, hepatoprotective and neuroprotective activity, and is capable of immune enhancement ( 9 , 10 , 14 16 ). In the present study, the HPLC chromatogram detected pectolinarin in the C. setidens extract.…”
Section: Discussionmentioning
confidence: 99%
“…We found that carvone decreased melanin content in a concentration-dependent manner ( Figure 1B,C). We recently conducted a phenotype-based approach to screening for compounds in B16F10 melanoma cells to find small-molecule inhibitors of melanin synthesis [16,17]. By this method, we found that carvone treatment markedly decreases melanin content.…”
Section: Carvone Decreases Melanin Content Of B16f10 Melanoma Cellsmentioning
confidence: 99%